Heart rate response during a simulated Olympic boxing match is predominantly above ventilatory threshold 2: a cross sectional study - de Lira, C. A.; Peixinho-Pena, L. F.; Vancini, R. L.; Fachina, R. J.; de Almeida, A. A.; Andrade, M. S.; da Silva, A. C. (Open Access Journal of Sports Medicine, 2013)
The present study aimed to describe heart rate (HR) responses during a simulated Olympic boxing match and examine physiological parameters of boxing athletes. Ten highly trained Olympic boxing athletes (six men and four women) performed a maximal graded exercise test on a motorized treadmill to determine maximal oxygen uptake (52.2 mL · kg-1 · min-1 ± 7.2 mL · kg-1 · min-1) and ventilatory thresholds 1 and 2. Ventilatory thresholds 1 and 2 were used to classify the intensity of exercise based on respective HR during a boxing match. In addition, oxygen uptake (VO2) was estimated during the match based on the HR response and the HR-VO2 relationship obtained from a maximal graded exercise test for each participant. On a separate day, participants performed a boxing match lasting three rounds, 2 minutes each, with a 1-minute recovery period between each round, during which HR was measured. In this context, HR and VO2 were above ventilatory threshold 2 during 219.8 seconds ± 67.4 seconds. There was an increase in HR and VO2 as a function of round (round 3 < round 2 < round 1, P < 0.0001).These findings may direct individual training programs for boxing practitioners and other athletes.